PERANCANGAN PENGAMANAN SERVER SECARA OTOMATIS MENGGUNAKAN METODE ADAM (AUTOMATIC EVENT DETECTION AND ACTIVITY MONITORING) - Kusumaningrum, Anggraini; Sianturi, Rolas (Compiler, 2015)
In an era like today's global, Internet-based information system security is a must to be considered, because of the public nature of the internet network and global is not safe. Basically the threat is coming from someone who wishes mempuyai gain illegal access to a computer network. Whenever there is a threat encountered on the server such as port scanning, the attacker IP addresses will be captured. Next will be used method Automatic Event Detection And Activity Monitoring (ADAM) to process security. ADAM will carry out retaliatory attacks in the form of a computer virus that was sent to the attacker. For this reason when a computer network is attacked by the intruder, then ADAM server will detect this type of attack is done, then asked for help from another server to strike back. Security server by applying the method ADAM able to do the blocking of port scanning the attacker did not end there ADAM will then send the file is a virus automatically. In terms of time efficiency, the method of securing the ADAM automatically faster than if all phases of the security is done manually. ADAM test non-adaptive systems this takes 4.4 minutes, while the time taken by the ADAM system to immobilize the attacker system only 1 minute 03:59 seconds, so the method ADAM work faster. Traffic normal state (RX 232B, 144B TX), but when encountered in the form of port scanning attacks become 21.46Kib TX RX 25.83Kib, and after working as RX 219B ADAM TX127B, resulting in a significant reduction in traffic.